Early Late Triassic retro-foreland basin in response to flat subduction of the Paleo-Tethyan oceanic plate, SE Tibet - Liang, Mingjuan; Yang, Tiannan; Yan, Zhen; Xue, Chuandong; Xin, Di; Qi, Shaofeng; Dong, Mengmeng; Wang, Wei; Shi, Pengliang; Xiang, Kun; Han, Xue; Bao, Jingkun (Frontiers in Earth Science, 2022)
Syn-subduction basins bear significant implications to understand tectonic evolution of any fossil subduction zone. The late Paleozoic to early Mesozoic (Paleo-Tethyan) tectonics of the eastern and southeastern Tibetan Plateau (i.e., the Sanjiang Orogenic Belt) is featured by ocean-continent subduction systems. A huge pile of volcanic-absent sedimentary succession developed in the middle segment of the Sanjiang orogenic belt, its age and tectonic nature remain unclear. Detailed geological mapping and zircon U-Pb dating results demonstrate that the early Late Triassic volcanic-absent succession comprises the nonmarine Maichuqing Formation in the lower part and the shallow marine Sanhedong Formation in the upper part. The Maichuqing Formation consists of coarse to fine-grained sandstone, siltstone and mudstone with abundant basal erosional surfaces, trough and planar cross-beddings, ripples, mudcracks, and plant fragments. The Sanhedong Formation comprises predominantly bioclastic limestones interlayered with marl, calcareous-muddy siltstone, and calcareous sandstone with abundant bivalve fossils. Syn-sedimentation deformation structures, such as slump folds and associated normal faults are common, suggesting intense tectonism during deposition. Synthesizing sedimentary data, paleocurrent and provenance results, combined with other available data, demonstrate that the volcanic-absent succession deposited within a retro-foreland basin along the rear part of the Permian-Triassic Jomda-Weixi-Yunxian arc in response to flat-subduction of the Paleo-Tethyan Ocean during the early Late Triassic time.